Mastering Arabic Vocabulary through Drill Technique: A Study on Primary Learners - Hasan; Olsafrian Ihsanu Matswa; Muhammad Gatan Arda Saputra (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
Vocabulary acquisition is fundamental to mastering a second language, especially at the primary education level where learners are building their linguistic foundation. This study explores the effectiveness of the drill technique in enhancing Arabic vocabulary retention among fourth-grade students at an Islamic primary school. Using a qualitative descriptive approach, the research involved 60 students over a four-week period, employing classroom observations, interviews, and document analysis. The findings reveal that structured and repetitive drills, when implemented with contextual relevance and learner engagement, significantly improve vocabulary recall and student motivation. Moreover, the method’s low-resource demands make it highly suitable for underfunded or traditional learning environments. By reintroducing drill-based instruction as a viable pedagogical strategy, this study contributes both practical and theoretical insights into Arabic language education for young learners.